COMPARATIVE ANALYSIS OF THE SMALL LIFE CYCLE OF PERENNIAL FORAGE GRAINS IN THE FOOTHILLS OF UZBEKISTAN (Scientific journal of the Fergana State University, 2024)
This article analyzes the small life cycle of perennial cereals in the adyr zones of the Republic of Uzbekistan. As a result of the analysis of the results obtained, it was noted that the maximum lifespan of the maternal shoot (p+I) in Agropyron cristatum and Hordeum bulbosum is 25-26 months, and in Elytrigia trichophora up to 4 years. In Hordeum bulbosum, the first and second shoots p+2 die off along with the mother shoot, i.e. Their lifespan is 10-18 months. In Agropyron cristatum, the 1st and 2nd shoots p+2 remain viable for two years, and in Elytrigia trichophora for 3-4 years.